Morpho-cultural and molecular characterization of trichoderma species from the northwestern himalayan apple rhizosphere of India - Sana Surma; Sumaira H.; Misbah M.; M. S. Dar; Bilal A. Padder; Imran Khan; Khalid Mushtaq; Maheen M.; Sehla K.; Asha Nabi; Mushtaq A. Lone; Snober S. Mir; et al. (Scientific Reports)
Abstract Plant disease management based on pesticide use has numerous detrimental effects on health and the environment. As a result, the adoption of environment-friendly disease management options is the best alternative to pesticide use. Therefore, the identification of locally available bio-agents like Trichoderma species using morpho-cultural and molecular approaches specifically targeting the internal transcribed spacer (ITS) region, translation elongation factor 1-alpha (TEF 1-α) and RNA polymerase B subunit II (RPB2) is necessary. In this study, we characterized 24 Trichoderma strains isolated from the apple rhizosphere. Significant variations were observed in the morpho-cultural characteristics of Trichoderma isolates and categorized them into four groups (I-IV) that were identified as T. harzianum complex, T. koningiopsis, T. viride, and T. hamatum, comprising 4, 4, 6 and 10 isolates, respectively. The concatenated sequence data set derived from the ITS region, TEF 1-α and RPB2 grouped 24 Trichoderma isolates into 03 independent clades. Specifically, the sequencing based on ITS region grouped them into four sub-clades, which were identified as T. harzianum complex, T. viride, T. asperelloides, and T. koningiopsis, comprising 4, 6, 5 and 7 isolates, respectively, and two independent lineages, each represented by a single isolate. In contrast, sequencing of the TEF 1-α and RPB2 genes grouped 24 Trichoderma isolates into two distinct clades and six sub-clades that were identified as T. asperelloides, T. asperellum, T. hamatum, T. viride, T. koningiopsis and T. harzianum complex, comprising 5, 5, 3, 4, 3 and 4 isolates, respectively. Thus, the final identification of 24 Trichoderma strains was achieved through a combined morpho-cultural and molecular approach, resulting in the identification of six species viz., T. koningiopsis, T. viride, T. asperellum, T. asperelloides, T. hamatum and T. harzianum complex comprising 5, 5, 3, 4, 3 and 4 isolates, respectively in accordance with the reference sequences retrieved from NCBI. Notably, to our knowledge, this is the first report of T. koningiopsis, T. viride, T. asperellum, T. asperelloides, and T. hamatum from the apple rhizosphere.